A Study of Corporate Training Evaluation Using Andragogy Principles - Fallahi, Mehdi; Mohammad Rezaei, Ali; Delavarpour, Mohammad Agha (Iranian Journal of Educational Sociology, 2025)
The objective of this research was to examine employee participation and motivation in the training evaluation process within corporate settings, using principles of andragogy. The study employed the qualitative methodology of the Grounded theory. The research focused on employees at the Pardis Petrochemical Company in Asaluyeh, located in the Bushehr province of Iran. A purposive sampling technique was used to select 15 middle managers and experts, ensuring theoretical saturation. In-depth semi-structured interviews were conducted to collect data, which were subsequently analyzed using coding based on the Grounded theory using MAXQDA version 18 software. A total of 224 codes were identified during the open coding process, which were then carefully categorized into seven axial codes related to the post-training stage. A causal relationship model was developed based on these codes, illustrating the connections between categories, specifically emphasizing the interrelated concepts of mindfulness, motivation, and participation. The model identified two causal categories associated with mindfulness,